PENGARUH MODEL CTL (PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING) BERBASIS MULTIPLE INTELLIGENCE TERHADAP KETERAMPILAN PROSES SAINS SISWA KELAS V SDN SEPATHI PURWOREJO - Elvina Zulaikhah; Rasidi (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This study aimed to determine the effect of the Multiple Intelligence-Based CTL (Contextual Teaching And Learning) Model on the students’ Science Process Skills at grade V of SD Negeri Sepathi Purworejo. This study was a quantitative pre-experimental one-group pretest-posttest design. The population and samples of this study were 21 fifth-grade students at SDN Sepathi, consisting of 7 male students and 14 female students. The data collection was carried out using multiple-choice test instruments, consisting of 14 questions and observation sheets. The SPSS 22 program processed the data with nonparametric statistical test analysis using the Wilcoxon test. This study found the value of Asymp. Sig 2-tailed of 0.001. Thus, Ha was accepted. This study concluded that the MI (Multiple Intelligence)-based CTL (Contextual Teaching and Learning) Model influenced the students’ Science Process Skills at grade V of SD Negeri Sepathi Purworejo.